2014
DOI: 10.1007/s11010-014-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid promotes myocardial antioxidant response and prevents isoproterenol-induced myocardial oxidative stress and apoptosis in mice

Abstract: quinine oxidoreductase 1, superoxide dismutase, catalase, nuclear translocation of Nrf2 and protein expression heme oxygenase-1 were evaluated. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and myocardial expression of cleaved caspase-3, caspase-9, p53, Bax, and Bcl-2 were investigated to assess the apoptotic cell death. Pretreatment with carnosic acid attenuated ISO-induced elevated serum levels of Troponin I, CK-MB, LDH, SGOT and SGPT, and histopathological alterations in heart. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 40 publications
4
38
1
Order By: Relevance
“…Rosemary can mimic SOD by removing superoxide radicals[58], which could also explain the lower enzyme activity in cardiac tissue of the supplemented groups. No effect of rosemary was observed on Nrf-2 and HO-1 expression, different from what we expected and from previous reports showing Nrf2 activation after treatment with rosemary compounds[59, 60]. One possible explanation is that in some pathological situations, as in hypoxia, Nrf-2 does not increase.…”
Section: Discussioncontrasting
confidence: 99%
“…Rosemary can mimic SOD by removing superoxide radicals[58], which could also explain the lower enzyme activity in cardiac tissue of the supplemented groups. No effect of rosemary was observed on Nrf-2 and HO-1 expression, different from what we expected and from previous reports showing Nrf2 activation after treatment with rosemary compounds[59, 60]. One possible explanation is that in some pathological situations, as in hypoxia, Nrf-2 does not increase.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous investigation has revealed carnosic acid may attenuate the isoproterenol-induced myocardial injury in a mouse model through preventing oxidative stress and apoptosis (17). In the present study, the investigations performed further elucidated the protective effects of carnosic acid on myocardial injury in vitro, which is reported in H9c2 cardiomyocytes for the first time.…”
Section: Discussionsupporting
confidence: 62%
“…Previous pharmacological studies have demonstrated that carnosic acid affords various biological activities, such as neuroprotection (11), prevention of advanced glycation end-product formation (12), attenuation of Alzheimer's disease (13), anticancer activity (14), anti-inflammation (15) and renoprotection (16). Furthermore, carnosic acid presented a cardioprotective effect in an isoproterenol-induced myocardial stress mouse model via preventing oxidative stress and apoptosis (17).…”
Section: Introductionmentioning
confidence: 99%
“…Considering all these reports, there is a clear body of evidence to support the potential of simultaneous activation of Nrf2 and eNOS as a therapeutic target in the prevention of cardiac diseases. [109] Maslinic acid Triterpene Coleus tuberosus [110] Triphlorethol-A Phlorotannin Ecklonia cava [111] Tanshinone IIA Phenanthrenequino ne Salvia miltiorrhiza [112] Schisandrin B Dibenzocyclooctad iene Saururus chinensis [113] α-Lipoic Acid Vicinal dimercaptans Vegetables and fruits [114] Sulforaphane Isothiocyanates …”
Section: Activators Of No-nrf2/are Pathway For the Protection Againstmentioning
confidence: 99%